COMMUNICATIONS SKILLS OF STUDENTS THROUGH ELECTRONIC MESSAGING STUDY CASE : STUDENTS OF STMIK STIKOM (STIKI) INDONESIA - Ni Putu Suci Meinarni; Ayu Gede Willdahlia (Universitas Sebelas Maret, 2017)
Communication through short messages (SMS) is one of the communication’s obstacles between lecturers and students. These issue could indirectly lead to misunderstandings between students and lecturers. This is caused by various factors, the important one is because the communication can not be done face-to-face, it may cause prejudices or negative perceptions. In this research, we are trying to summarize communication pattern through SMS between lecturers with STMIK STIKOM (STIKI) Indonesia students as sample. From the data we have collected, we concluded that there are still some students lack of intelligence in sending short messages. It is important to educate about the ethics of communication, because it is the basic human capital to interact with other humans.